Some Remarks on Western and Islamic Perceptions of the Law: With a Reference to the Right to Freedom of Speech - Scatolini Apostolo, Sergio AbdusSalam (Afkar: Jurnal Akidah dan Pemikiran Islam, 2010)
In this article, the author outlines some of the fundamental differences between the Islamic and the Western legal cultures (the issue of freedom of speech being an example thereof). On the one hand, the Western view of the law is mostly contractual (even despite the fact that the Western human rights discourse makes a strong metaphysical claim by implying that these rights are (quasi) natural and not merely contractual). On the other hand, the Islamic viewpoint rests on the belief of divine creation: the only One Who can create, can also stipulate what is right or wrong in creation. All in all, the fundamental differences between the Islamic and the Western legal traditions do not prevent them from often producing similar norms or seeking the realization of similar values.